Critical role of the IgM Fc receptor in IgM homeostasis, B-cell survival, and humoral immune responses - Ouchida, Rika (National Academy of Sciences, 2012)
IgM antibodies have been known for decades to enhance humoral immune responses in an antigen-specific fashion. This enhancement has been thought to be dependent on complement activation by IgM–antigen complexes; however, recent genetic studies render this mechanism unlikely. Here, we describe a likely alternative explanation; mice lacking the recently identified Fc receptor for IgM (FcμR) on B cells produced significantly less antibody to protein antigen during both primary and memory responses. This immune deficiency was accompanied by impaired germinal center formation and decreased plasma and memory B-cell generation. FcμR did not affect steady-state B-cell survival but specifically enhanced the survival and proliferation induced by B-cell receptor cross-linking. Moreover, FcμR-deficient mice produced far more autoantibodies than control mice as they aged, suggesting that FcμR is also required for maintaining tolerance to self-antigens. Our results thus define a unique pathway mediated by the FcμR for regulating immunity and tolerance and suggest that IgM antibodies promote humoral immune responses to foreign antigen yet suppress autoantibody production through at least two pathways: complement activation and FcμR.